Early Growth Response Factor 1 in Aging Hematopoietic Stem Cells and Leukemia - Kulkarni, Rohan (Frontiers in Cell and Developmental Biology, 2022)
Aging is associated with various hematological disorders and a higher risk of myeloproliferative disorders. An aged hematopoietic system can be characterized by decreased immune function and increased myeloid cell production. Hematopoietic stem cells (HSCs) regulate the production of blood cells throughout life. The self-renewal and regenerative potential of HSCs determine the quality and quantity of the peripheral blood cells. External signals from the microenvironment under different conditions determine the fate of the HSCs to proliferate, self-renew, differentiate, or remain quiescent. HSCs respond impromptu to a vast array of extracellular signaling cascades such as cytokines, growth factors, or nutrients, which are crucial in the regulation of HSCs. Early growth response factor 1 (EGR1) is one of the key transcription factors controlling HSC proliferation and their localization in the bone marrow (BM) niche. Downregulation of Egr1 activates and recruits HSCs for their proliferation and differentiation to produce mature blood cells. Increased expression of Egr1 is implicated in immuno-aging of HSCs. However, dysregulation of Egr1 is associated with hematological malignancies such as acute myeloid leukemia (AML), acute lymphoblastic leukemia (ALL), and chronic myelogenous leukemia (CML). Here, we summarize the current understanding of the role of EGR1 in the regulation of HSC functionality and the manifestation of leukemia. We also discuss the alternative strategies to rejuvenate the aged HSCs by targeting EGR1 in different settings.